Thelma [videorecording (DVD)] - Margolin, Josh (Film director); Margolin, Josh (Film director); Squibb, June, 1929-; Hechinger, Fred; Roundtree, Richard, 1942-2023; Gregg, Clark, 1962-; Posey, Parker, 1968-; McDowell, Malcolm, 1943-; Bolen, David (Magnolia Home Entertainment, 2024)
Inspired by a real-life experience of the director, an elderly grandmother is an unlikely action hero, demonstrating that she is more than capable of taking care of business despite what her daughter Gail, son-in-law Alan, or grandson Danny might believe. After getting conned by a phone scammer preteneding to be her grandson, Thelma enlists the help of an old friend and sets out to take back what's hers.